Economical role of boreal forests in the European North of Russia - Valentina Zhideleva; Nikolay Bolshakov (European Regional Science Association (ERSA), 2013)
Last century was marked by the rapid economical and scientific development: population increased by five-six times, energy use in the developed countries increased by hundred times, pollution of atmosphere and soil caused by technogenic emissions became global. Most fears among the scientists and politicians are dealing with the evident climate warming, which is exhibited in the northern regions. Against this background, the researches about the leading role of boreal forests in the carbon balance in giogeocenoses on land and regional economics attract a lot of interest. The analysis of the European forest fund and boreal forests of the Russian European North, including the Komi Republic was made and we developed the action plan, aiming at more efficient and careful use of boreal forests. Natural complex of the north European boreal forests ? is a unique natural unit, which plays the global biospheric role in the ecological balance control on the continent. It?s quite practical to make the international project ?Boreal forests of the European north? in order to preserve their ecological and protective role. Special attention should be paid to the boreal forests monitoring, by creating the integrated boreal forests monitoring system in both Western and Eastern Europe and the fact that in North-East of Europe, in the Cis-Ural region of Komi, there are remained huge pristine forest areas should be taken into account. Considering the great ecological and economical significance of the boreal forests, it?s very important to make the proposal about the international cooperation in rational use based on sustainable principles and productivity increase. Among the northern forest regions of the European North, the forest fund of the Komi republic attracts special attention, as it comprises the forth part of the forest covered boreal area and the tenth part of the total European forest area. Figuratively speaking, every tenth tree on the continent grows in the Komi republic. At the same time, nature protected areas make 1/3 of all forests in the republic and almost 40 mln hectors of forest covered area of the Komi republic make the landfill for carbon and are actively involved in the biospheric balance. The potential of the Boreal forests is worth a more detailed research, and will definitely play the important role in the development of the European North in the future.
Keywords: 330; Sustainable development; forest management; forest fund; sustainable forest management; forest use; timber harvesting; annual allowable cut; intensive forest management; pristine forests; recreational forest use; boreal forests